Measuring the efficacy of a project for adolescents and young adults with cancer: A study from the Milan Youth Project. Issue 12 (24th August 2016) - Ferrari, Andrea; Silva, Matteo; Veneroni, Laura; Magni, Chiara; Clerici, Carlo Alfredo; Meazza, Cristina; Terenziani, Monica; Spreafico, Filippo; Chiaravalli, Stefano; Casanova, Michela; Luksch, Roberto; Catania, Serena; et al.
ABSTRACT: Background: Various projects dedicated specifically to adolescents and young adults (AYA) with cancer have been developed in recent years. A critical aspect of such programs is the ability to demonstrate its value, and therefore how to measure desired outcomes. Methods: A list of metrics to consider for demonstrating the advantages of an AYA program was identified and used to assess the activity of the Youth Project operating at the Pediatric Oncology Unit of the Istituto Nazionale Tumori in Milan. Results: The number of newly diagnosed AYA patients seen at the Unit has increased since the formal launch of the Youth Project, from 65 to 81.2 cases/year. Concerning the 78 AYA patients presenting with malignant neoplasms in 2015, 82% were included in clinical trials (the other 18% in prospective observational studies). Fertility preservation measures were implemented for 59% of AYA patients considered at risk, and specific psychological support was provided in 70.6% of cases; 72.5% of patients actively participated in support activities. Other parameters considered were a preliminary satisfaction questionnaire administered to patients and the program's scientific recognition and acknowledgment by the community. Conclusions: The study proposed a number of potentially reproducible, practical parameters to consider in assessing the value of a program dedicated to AYA. These metrics were examined in terms of the activities of our Youth Project, and confirmed its efficacy. To be sustainable over time, AYA projects have to be accepted as a standard of care at the community and government levels.